Determinants of The Demand for Money in Iraq (Econometric Study) - Helmy Ibraheem Menshad ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
This paper is an attempt to analyze and measure the demand function for real money in Iraq according to a multivariate time series framework, using Cointegration tests by Johansen’s Approach and the Error Correction Vector Model (VECM), assuming the interdependence between the determinants of money demand as nonstationary variables. This helped to understand the behavior of the demand for money in Iraq for the period (2004-2020), and to reveal the moral effect among the variables included in the system of the Autoregressive Vector(VAR). The estimation of the function of demand in the long run indicates the low speed of adjustment in getting rid of the imbalance. The Empirical results of the research indicated that the exchange rate, government spending and the general level of prices explain most of the changes in the demand for money in the long run. In the short term, only the exchange rate had a significant effect on the function of demand for money in Iraq, but the rest of the other variables failed to explain the behavior of this function during the short period.